Sosialisasi Mewujudkan Siswa Kreatif dan Mandiri Melalui Kewirausahaan Desain Grafis Digital Di SMK Negeri 1 Nogosari - Fitria Ambarsari; Fika Arum Lestari; Foundra Izza Al Hafizh; Ferulina Keysha Azzahra; Luki Sri Anggorowati (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
The rapidly evolving digital era has brought significant changes, particularly in enhancing the knowledge, creativity, and digital entrepreneurship skills of students at SMK Negeri 1 Nogosari through digital graphic design outreach and training. This outreach program aims to enhance the entrepreneurial competencies of SMK Negeri 1 Nogosari students through intensive digital graphic design training using the Canva application. Digital entrepreneurship is the practice of building and running a business whose operations rely primarily on digital technology. Its spectrum is broad, encompassing everything from e-commerce and mobile applications to social media, cloud computing, and big data analysis. The outreach activities at SMK Negeri 1 Nogosari utilized a program implementation method that included a participatory approach through material delivery (interactive lectures), hands-on practice using easily accessible graphic design applications (such as Canva), and interactive discussions. Keywords: Entrepreneurship, Canva, Digital Graphic Design, SMK Negeri 1 Nogosari.